EFEKTIVITAS MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PENDIDIKAN PANCASILA KELAS 3 SD - Salma, Farida Azka; Hamidaturrohmah (Universitas Negeri Medan, 2025)
Learning can run smoothly if in its implementation using an innovation model that suits the needs of students. This study aims to evaluate the effectiveness of the problem based learning (PBL) learning model in improving critical thinking skills of grade 3 students in the Pancasila Education subject. at SDN Potroyudan. The research method used is quantitative research pre-experimental design type one group pretest-posttest. Data collection techniques include observation, interviews, questionnaires and tests. The results of the study indicate that the use of the problem based learning (PBL) learning model in grade 3 students has proven effective in improving critical thinking skills. The results were obtained from an average pretest score of 34.62 to 95.38. The difference in value between the pretest and posttest was 60.76 with an increase of around 175.51%. Based on the Paired Sample T-Test test, it shows that the difference between the pretest and posttest scores is very significant with a t value = -11.262 and p-value = 0.000, which is smaller than 0.05. This shows that the problem based learning (PBL) model has a positive impact on improving students' critical thinking skills. In addition, the results of the N-Gain test showed a very good increase with an average N-Gain of 0.9443, which is included in the high category.